A case-matched series comparing functional outcomes for robotic-assisted unicompartmental knee arthroplasty versus functionally aligned robotic-assisted total knee arthroplasty - Jonathan R. Manara; Macdaniel Nixon; Beth Tippett; Wil Pretty; Dermot Collopy; Gavin W. Clark (Bone & Joint Open)
Aims: Unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) have both been shown to be effective treatments for osteoarthritis (OA) of the knee. Many studies have compared the outcomes of the two treatments, but less so with the use of robotics, or individualized TKA alignment techniques. Functional alignment (FA) is a novel technique for performing a TKA and shares many principles with UKA. Our aim was to compare outcomes from a case-matched series of robotic-assisted UKAs and robotic-assisted TKAs performed using FA. Methods: From a prospectively collected database between April 2015 and December 2019, patients who underwent a robotic-assisted medial UKA (RA-UKA) were case-matched with patients who had undergone a FA robotic-assisted TKA (RA-TKA) during the same time period. Patients were matched for preoperative BMI, sex, age, and Forgotten Joint Score (FJS). A total of 101 matched pairs were eligible for final review. Postoperatively the groups were then compared for differences in patient-reported outcome measures (PROMs), range of motion (ROM), ability to ascend and descend stairs, and ability to kneel. Results: Both groups had significant improvements in mean FJS (65.1 points in the TKA group and 65.3 points in the UKA group) and mean Oxford Knee Score (OKS) (20 points in the TKA group and 18.2 in the UKA group) two years following surgery. The UKA group had superior outcomes at three months in the OKS and at one year in ROM (5°), ability to kneel (0.5 points on OKS question), and ascend (1.3 points on OKS question) and descend stairs (0.8 points on OKS question), but these were not greater than the minimal clinically important difference. There were no differences seen in FJS or OKS at one year postoperatively. There were no statistically significant differences between the groups at 24 months in all the variables assessed. Conclusion: FA-RATKA and RA-UKA are both successful treatments for medial compartmental knee arthritis in this study. The UKA group showed a quicker recovery, but this study demonstrated equivalent two-year outcomes in all outcomes measured including stair ascent and descent, and kneeling. Cite this article: Bone Jt Open 2024;5(12):1123–1129.